SAH-Induced Electrophysiological Changes of Ventricular Myocytes and Role of N-acetylcysteine Protection - Ayaz, Murat; Yanardag, Sirma Basak (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Electrocardiogram (ECG) changes in patients with subarachnoid hemorrhage (SAH) are frequent. ST- and/or T-wave changes in ECG seem to predominate.Study Aims To investigate the ion channel mechanisms of SAH-induced ventricular excitation-contraction coupling changes and the possible protective effect of N-acetylcysteine (NAC).Methods Three groups of rabbits were used for the experiments. In two groups, SAH was induced by replacing the cerebrospinal fluid (CSF) with fresh autologous blood. In the control group, CSF was replaced with isotonic saline. In one SAH group, NAC was administered daily beginning at SAH induction. On day 5, ventricular action potentials, ionic currents, contractions, and intracellular free ion concentrations were recorded from the myocytes.Results In the SAH group, no change was found in the sodium currents, but the transient outward potassium currents were depressed, rapid repolarizing currents were increased, and t-type calcium currents were increased. Contractions and the intracellular free calcium concentration were depressed. NAC treatment, in contrast, not only restores these electrical remodeling changes but also the contractile abnormalities in the cardiac myocytes.Conclusion The changes in the action potential duration can be attributed to the measured ionic current changes. However, the exact mechanism, other than the oxidative stress, by which the NAC treatment protects the cardiac muscle needs additional investigations.
Keywords: action potential; ionic currents; myocyte; N- acetylcysteine; subarachnoid hemorrhage